Effect of thermo-physical parameters on heat transfer characteristics of the wall implanted with heat pipes. (25th June 2022) - Zhang, Zhigang; Wang, Yu; Yao, Wanxiang; Gao, Feng; Shou, Chunhui
Highlights: A new evaluate index (ITRR) is proposed to reflect the thermal response. The actual environmental of WIHP dynamic experiment system is tested and validation. The influence of thermal conductivity on the heat transfer of WIHP is analyzed. The influence of density on the heat transfer of WIHP is analyzed. The influence of specific heat capacity on the heat transfer of WIHP is analyzed. Abstract: The heat transfer characteristics of a wall implanted with heat pipes (WIHP), a new passive natural energy utilization technology, significantly differ from that of an ordinary wall. It features effective heat transfer between indoor and outdoor environments due to the pipe's unidirectional thermal conductivity. The thermal performance of the wall is crucial in terms of reducing a building's energy consumption. In this paper, the experiment and theoretical analysis were combined, and the numerical simulation calculation was used to analyze the effects of material thermo-physical parameters on WIHP heat transfer performance. The results show that for the inside surface temperature, density and specific heat capacity are negatively related to it, and thermal conductivity is also negatively related to it before the heat pipe is in optimum working condition, and then the thermal conductivity is positively related to it. For the inside surface heat flux, it is opposite to the variation of inside surface temperature. The inside surface temperature rise rate (ITRR) is proposed to reflect the thermal response of the inside surface temperature to the variation of outdoor air temperature. When the thermal conductivity increases, the difference between the maximum and minimum ITRR is 0.053 °C/h. When the density increases, the trend of ITRR decreases first and then increases, and the average value is 0.062 °C/h. When the specific heat capacity gradually increases, the difference between the maximum and minimum of ITRR is 0.006 °C/h.